Multicultural Islamic Ethics Education for Women as a Prevention of Corruption Practices in Daily Life - Dwi Ari Kurniawati; Khoiriyah Trianti (Jurnal Ijtihad, 2023)
Corruption is a serious "disease" that befalls or tests the resilience of the Indonesian people. In any region and in institutional units related to state financial management, both from the central and regional levels, corruption almost always follows. As if where there is state money, that's where corruption appears. As a result of this condition, all subjects of the nation, especially those who feel they have a moral obligation to try to do prevention or prevention. Women are the subject of an educated nation who also have such an obligation, so it is logical that there is strengthening of Islamic ethical education on anti-corruption.